KAJIAN RESIKO USAHA PENGOLAHAN IKAN TERI DI DESA PAGURAWAN, KECAMATAN MEDANG DERAS, KABUBAPATEN BATUBARA, PROVINSI SUMATERA UTARA - Sirait, Melva Dumaria; Purwoko, Agus (Jurnal AGRISEP, 2012)
This research was done in Desa Pagurawan, Kec. Medang Deras, Kab. Batubara, Provinsi North Utara. The aim of this research were to calculate income of the anchovy’s processing business and to analyze it’s business risks. All the businessmen of anchovy (32 respondents) were selected by cencus method. The data analysis method used the descriptive analysis and the method of E-V analysis. The research results showed that the income of anchovy processing business was Rp. 5,437,283 per week. The variation coeficient (CV) of the anchovy processing business was 0.04 with the value of the limit lower income (L) was Rp. 5,055,889.11 in a week. If the value of CV ? 0.5 and the value of L ? 0, these mean that the business risk’s anchovy processing was lower and the opportunities for getting the profit was high.